Dramatic Increase in Incidence of Ulcerative Colitis and Crohn's Disease (1988–2011): A Population‐Based Study of French Adolescents. (February 2018) - Ghione, Silvia; Sarter, Hélène; Fumery, Mathurin; Armengol‐Debeir, Laura; Savoye, Guillaume; Ley, Delphine; Spyckerelle, Claire; Pariente, Benjamin; Peyrin‐Biroulet, Laurent; Turck, Dominique; Gower‐Rousseau, Corinne; Andre, J M; et al.
Abstract : OBJECTIVES: Few data are available to describe the changes in incidence of pediatric‐onset inflammatory bowel disease (IBD). The aim of this study was to describe changes in incidence and phenotypic presentation of pediatric‐onset IBD in northern France during a 24‐year period. METHODS: Pediatric‐onset IBD (<17 years) was issued from a population‐based IBD study in France between 1988 and 2011. Age groups and digestive location were defined according to the Paris classification. RESULTS: 1, 350 incident cases were recorded (8.3% of all IBD) including 990 Crohn's disease (CD), 326 ulcerative colitis (UC) and 34 IBD unclassified (IBDU). Median age at diagnosis was similar in CD (14.4 years (Q1=11.8–Q3=16.0)) and UC (14.0 years (11.0–16.0)) and did not change over time. There were significantly more males with CD (females/males=0.82) than UC (females/males=1.25) ( P =0.0042). Median time between onset of symptoms and IBD diagnosis was consistently 3 months (1–6). Mean incidence was 4.4/10 5 for IBD overall (3.2 for CD, 1.1 for UC and 0.1 for IBDU). From 1988–1990 to 2009–2011, a dramatic increase in incidences of both CD and UC were observed in adolescents (10–16 years): for CD from 4.2 to 9.5/10 5 (+126%; P <0.001) and for UC, from 1.6 to 4.1/10 5 (+156%; P <0.001). No modification in age or location at diagnosis was observed in either CD or UC. CONCLUSIONS: In this population‐based study, CD and UC incidences increased dramatically in adolescents across a 24‐year span, suggesting that one or more strong environmental factors may predispose this population to IBD.